Advances in the management of pleural disease. - Corcoran, J; Hallifax, R; Rahman, N (2013)
Pleural disease affects over 3000 people per million population annually. Consequently, it represents a significant proportion of the respiratory physician's workload and can present to clinicians of all backgrounds in primary and secondary care. Pleural effusions have been reported in association with over 50 different conditions; some related to specific pulmonary pathologies, but many being manifestations of multisystem disease. The burden that conditions such as pleural infection; malignant pleural disease; and pneumothorax impose on patients and health care systems is enormous and growing. As such, a clear understanding of these key conditions is crucial to any physician regardless of the specialty. This article addresses a number of areas relating to pleural disease, providing an overview of the diagnostic and therapeutic advances that have been made in our understanding of pleural pathology in recent years. The directions that future research in this important area of respiratory medicine might take will also be discussed.